NEUROPSYCHOLOGICAL BASES OF MORALITY - Avdulova, T. P. (Modern Psychology, 2019)
The empirical research of the neuropsychological bases of moral development was conducted on sample of 82 children at preschool age. The interrelations between the moral sphere of the children and neuropsychological level were studied. Children with insufficient formation of neurostructures show the weak level of moral development. The following factors of a brain maturity were revealed: ability to hold and reproduce the program (dynamic actions); ability to estimate and reproduce rhythmic structures (acoustic gnosis); ability to a reencryption of the perceived image (visual and spatial actions). Besides, significant differences between boys and girls on neuropsychological indicators and level of following to external rules and also self-control level are found. In moral development the significant differences between boys and girls was not revealed. The low level of the neuropsychological organization was shown by the low level of selfcontrol in real situations at 44% of children.
Keywords: moral development, preschool age, neuropsychology, self-control, knowledge, actions.